(untitled) (The Pakistan Development Review, 2015)
Economic growth and development of the nations largely depend on the quantity and quality of their labour force. In Pakistan, a sizeable segment of population is considered as out of labour force. For instance, the overall labour force participation rate for the age 15 years and above remained roughly in the range of 49 percent to 53 percent during 1974-75 to 2012-13. This means that of the total population in 2012-13, aged 15 years and above, 53 percent is economically active or part of labour force whereas 47 percent is economically inactive or out of labour force. And more than 75 percent of the women population is considered as economically in-active. In addition, the labour market statistics show that a smaller proportion of women than men, age 15 years and above, are employed. The unemployment rate among women is higher than men. One of the possible explanations of this gender gap is gender discrimination in the labour market. In this context, this paper aims to analyse the behaviour of female and male in labour force participation by empirically investigating the determinants of labour force participation, and access to paid job for both female and male. It also shed light on occupational gender inequalities. It is believed that these types of analyses help designing better policies to increase employment opportunities for both females and males. They also facilitate suggesting various practical measures that can be incorporated in gender sensitised employment policies that in turn could lead towards greater labour force participation.